Riverine macroplastic gradient along watercourses: A global overview - Gallitelli, Luca; Scalici, Massimiliano (Frontiers in Environmental Science, 2022)
Nowadays, plastics represent a growing concern in aquatic habitats, harming more and more both ecosystem and human health. Since rivers are the main carriers of plastics to the sea, some studies were conducted on the transport of overall small plastics but observations on big plastics (i.e., macroplastics) in rivers are poorly reported in literature. Although most studies focused on plastic transport in the lower part of the rivers, research in the upper and middle zones are completely lacking. In this regard, this could influence the transport of plastics to the sea, with insights on the source and origin of macroplastics. Here, we aimed at overviewing macroplastic distribution along rivers, putting our emphasis on the global riverine plastic hot spot areas. Firstly, (i) we analysed and discussed the bibliometric analysis on macroplastics in rivers providing a framework for plastic pollution management. Then, (ii) we provided geographical insights on macroplastics mapping global riverine plastic hot spot areas. Thus, (iii) we analysed the main factors affecting macroplastic distribution and accumulation in rivers. Furthermore, (iv) we assessed crucial gaps in riverine macroplastic accumulation highlighting the importance of a plastic gradient in the horizontal transport along the entire river course (i.e. three river zones). Then, (v) we highlighted the lack of standardisation regarding macroplastic size, concentration, and polymers that does not allow valuable comparisons among studies. At the end, (vi) we concluded providing future perspectives and conclusions on macroplastic distribution and accumulation in rivers worldwide. Our results might provide new insights for a comprehensive framework of macroplastic distribution along global rivers, suggesting the river rod approach as a way for future monitoring as all the complete course of a river plays a pivotal role in accumulating macroplastics.